2021
DOI: 10.1002/jso.26655
|View full text |Cite
|
Sign up to set email alerts
|

Impact of stratified resection margin classification on local tumor control and survival in patients with oral squamous cell carcinoma

Abstract: Background Guidelines recommended for resection of oral cancer define a free margin of ≥5 mm as clear and safe (R0). This statement was questioned recently based on the assumption that different surgical margins may hold different risk categories. The aim of this study was to investigate the impact of stratification of the surgical margins on the survival outcome of patients with oral cancer. Methods In a cohort of 753 patients, the hazard ratio for local recurrence‐free survival (LRFS), overall survival (OS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Additional bias could affect the assessment of tumor borders and margins, including [ 131 ] their processing, and, eventually, lead to inadequate orientation of the tumor specimen—in many cases, aggravated by complex tumor shapes and sites. Furthermore, variable capacities in margin status prediction could result from the different intraoperative methods used to assess resection margins [ 127 ] and postresection shrinkage [ 131 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional bias could affect the assessment of tumor borders and margins, including [ 131 ] their processing, and, eventually, lead to inadequate orientation of the tumor specimen—in many cases, aggravated by complex tumor shapes and sites. Furthermore, variable capacities in margin status prediction could result from the different intraoperative methods used to assess resection margins [ 127 ] and postresection shrinkage [ 131 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional bias could affect the assessment of tumor borders and margins, including [ 131 ] their processing, and, eventually, lead to inadequate orientation of the tumor specimen—in many cases, aggravated by complex tumor shapes and sites. Furthermore, variable capacities in margin status prediction could result from the different intraoperative methods used to assess resection margins [ 127 ] and postresection shrinkage [ 131 ]. In particular, the reduction of tumor margin measurements (shrinkage), which occurs between the surgical pre-incision/excision processes and the histopathological evaluation [ 132 ], has been proposed as a potential cause for close pathological margins and requires prudential considerations by surgeons at the initial planning of resection margins.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery combined with immune checkpoint inhibitors, chemotherapy, and radiotherapy is the main treatment strategy for OSCC 2 . Studies have shown that up to 40% of patients have disease recurrence within 2 years after treatment 3,4 . Therefore, understanding the advancement of OSCC at the molecular level is indispensable for discovering new therapeutic targets for this disease.…”
Section: Introductionmentioning
confidence: 99%
“…2 Studies have shown that up to 40% of patients have disease recurrence within 2 years after treatment. 3,4 Therefore, understanding the advancement of OSCC at the molecular level is indispensable for discovering new therapeutic targets for this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Despite advancement in therapeutic interventions including adjuvant therapies with radiotherapy, systemic chemotherapy, and/or topical chemotherapy, an overall improvement on the 5-year survival rate in OSCC patients is still limited due to the aggressive local invasion and highly metastatic profile of OSCC [2][3][4][5]. Multiple cohort studies revealed that up to 40% of the patients experienced disease recurrence with increased tumor invasiveness within two years after completion of treatment [6][7][8]. Chemotherapy is the common choice of treatment of advanced OSCC for an overall improvement in the survival rate among patients.…”
Section: Introductionmentioning
confidence: 99%